Contribuição à citogenética de testudines e análise de assimetria flutuante em Eretmochelys imbricata, Cheloniidae - Marinho, Layse Aranha (2011)
This work has contributed to knowledge of the order Testudines from cytogenetic and morphological point of view. With regard to the aspects proposed cytogenetic characterization of the species Mesoclemmys tuberculata (n = 5), endemic to the Caatinga biomes, through conventional techniques of cytogenetics and molecular levels. This species presented 2n = 58, NF = 64, the first submetacentric pair, the second metacentric and third subtelocentric, and the other microchromosome telocentric. This species showed a nucleolar bearing pair, coincident with the 18S ribosomal rDNA and that proved to be heterochromatic. Small heterochromatic blocks were also found in the centromeres of the largest chromosomes, as well as terminal regions in most other chromosomes of the complement, that were GC +. Telomeric sequences showed variable patterns of signal intensity, with some repeats more intense in microchromosomes and subtly in the larger ones. When compared with other species of the genus, the G-banding patterns showed a marked similarity between them. The first karyotypic description of the species will aid in future studies and the understanding of evolutionary aspects of this family. From the morphological point of view, we carried out studies of fluctuating asymmetry in sea turtle Eretmochelys imbricata, using methods of benchmarking between hatchlings and adults and their implications for natural selection. Data were collected at two different times: first during the spawning female and the second during the outbreak and birth of the nest. The analyzed characteristics consisted of measurements of length and width of front and rear flippers (CANT, LANT, CPOS and LPOS) also collected data on the number of hull plates, side plates (NPL), the surrounding plates (NPCIRC), and plastron; plates power plants (NPP), inframarginais plates (NPIM). With the values of asymmetry we calculated the value of strict heritability for these traits, the calculation was based on only one parent. A nonparametric analysis Mann-Whitneywas performed to compare the groups (females X hatchlings, newborn hatchlings X dead hatchlings). Adult females showed no bilateral fluctuating asymmetry (FA = 0) on the number plates of the hull and plastron, while offspring, living and dead, showed a greater level of variation in these meristic parameters. In the analysis of females x hatchlings we found a significant difference between the levels of asymmetry in hoof plates (p=0.006) an the width of hindlimbs (p=0.001). Levels of FA suggest an accurate indicator as to the viability or maintenance of the individual to the reproductive phase. The coefficient of heritability (h2) of FA , obtained from the regression analysis, showed that both have low and not statistically significant values(p> 0.1). In the case of exclusion of the effective role of genetics in the generation of FA, reproductive strategies based on high number of subsidiaries products, such as those observed in E. imbricata seems to implicate the production of individuals with high level of developmental instability